How CETYS engineering is preparing its students for success - Algravez, Ana Melissa (My University, 2020)
The Centro de Enseñanza Técnica y Superior (CETYS University) is a private institution established in 1961 in Baja California, Mexico under the auspices of a group of visionary entrepreneurs committed to education. CETYS Engineering recognized in the spring of 2016 that it needed a formal organization to provide third-party, external feedback for the advancement of the CETYS College of Engineering. An Engineering Advisory Council (EAC) was formed that spring. At the May 2017 meeting of the EAC it asked: “What competencies are needed for the engineer of tomorrow?” “How is CETYS preparing its engineering students to meet this challenge?” These two simple questions lead to a year-long study conducted by the CETYS College of Engineering. With a broad industry survey resulting in a sample size of 42 subject matter experts (SME’s) we determined what are the most important Domains of Attributes, Skills and Abilities an engineer needs. Using this domain prioritization, we then learned “What are the biggest competency gaps?” that industry is finding in entry-level engineers today from all universities. Using this gap analysis, we then looked at the CETYS curriculum and determined that almost all of the gaps are overtly addressed in multiple classes. Finally, the survey led the CETYS College of Engineering to take action on how address those gaps
International Journal of Higher Education
Keywords: Engineering competency; Domains knowledge; Competency structured analysis tool; Campus Tijuana